1999
DOI: 10.1038/sj.onc.1203165
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-rays-induced death of human cells carrying mutations of BRCA1 or BRCA2

Abstract: There is now evidence to suggest that BRCA1 and BRCA2 are involved in the response of cells to DNA damage and cell cycle checkpoint control. This report examines the death pathways of human cells with various BRCA1 and BRCA2 genotypes after exposure to gamma-rays. A lack of functional BRCA1 and BRCA2 led to defective repair of DNA double-strand breaks in irradiated cells. This impairment resulted in a relaxation of cell cycle checkpoints, production of micronuclei, and a loss of proliferative capacity. Heteroz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(89 citation statements)
references
References 34 publications
7
77
0
2
Order By: Relevance
“…The question of whether genomic stability is adversely affected in the heterozygous BRCA condition has not fully been answered. However, our results suggesting that heterozygous mutations may possibly lead to haplotype insufficiency and genomic instability support previous data from Foray et al 11 These investigators demonstrated that irradiated EBV-immortalized lymphoblasts from BRCA carriers had a lower clonogenic survival, higher yields of micronuclei, less apoptosis and a greater degree of residual double-strand break defects following treatment with ionizing radiation. However, this study was based on only 9 immortalized cell lines with heterozygous BRCA mutations, so it also should be considered as preliminary data.…”
Section: Discussionsupporting
confidence: 91%
“…The question of whether genomic stability is adversely affected in the heterozygous BRCA condition has not fully been answered. However, our results suggesting that heterozygous mutations may possibly lead to haplotype insufficiency and genomic instability support previous data from Foray et al 11 These investigators demonstrated that irradiated EBV-immortalized lymphoblasts from BRCA carriers had a lower clonogenic survival, higher yields of micronuclei, less apoptosis and a greater degree of residual double-strand break defects following treatment with ionizing radiation. However, this study was based on only 9 immortalized cell lines with heterozygous BRCA mutations, so it also should be considered as preliminary data.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier studies employing lymphoblastoid cell lines with BRCA1 (or BRCA2) mutations demonstrated greater sensitivity to the chromosome damaging effects of g-radiation, and of hydrogen peroxide, compared to cells from healthy controls (as assessed by the micronucleus test or the radiation-induced chromatid break assay) (Foray et al, 1999;Speit et al, 2000). Recently, Trenz et al (2003aTrenz et al ( , 2005 demonstrated no difference in mutagen sensitivity using lymphoblastoid cell lines from women with and without a heterozygous BRCA1 mutation, thus highlighting the limitations of using cell lines to evaluate mutagen sensitivity and DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…BRCA1-deficient cells show sensitivity to ionizing radiation and drugs that produce double-strand breaks (DSB) or interstrand cross-linking agents, such as mitomycin C (13)(14)(15). Sensitivity to these agents, coupled with genetic instability, was also observed in cells with an exon 11 isoform of BRCA1 (16) and BRCA1-deficient embryonic stem cells (17).…”
Section: Brca1 Deficiency In Mice and Cultured Cellsmentioning
confidence: 99%